High-activity graphite felt for vanadium battery and preparation method of high-activity graphite felt

By using high-active graphite felts in all-vana liquid flow battery electrodes, the high-active graphite felts are formed by reacting with sulfur and molybdenum sources, the problem of insufficient catalytic and electrochemical activity of the existing electrodes is solved, and the vanadium battery is significantly improved energy and voltage efficiency.

CN119419292AInactive Publication Date: 2025-02-11HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510013778.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The catalytic and electrochemical activities of existing all-vanadium flow battery electrodes are low, resulting in low energy efficiency and voltage efficiency.

Method used

A highly active graphite felt for vanadium batteries is used to form a highly active graphite felt by reacting Ti3C2Tx with a sulfur source and a molybdenum source. The method includes dissolving lithium fluoride and aluminum titanium carbide in concentrated hydrochloric acid solution, then mechanically stirring and dispersing Ti3C2Tx in ethanol, adding sulfur and molybdenum sources to form a mixed liquid, and then impregnating the graphite felt and pyrolyzing to obtain a highly reactive graphite felt to obtain a highly reactive graphite felt. .

Benefits of technology

The energy efficiency and voltage efficiency of vanadium batteries are improved, and electrochemical performance is improved by increasing the layer spacing of Ti3C2Tx and doping S and molybdenum oxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419292A_ABST
    Figure CN119419292A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-vanadium redox flow battery electrodes, and discloses a high-activity graphite felt for a vanadium battery and a preparation method of the high-activity graphite felt. Comprising the following steps: selecting HCl and LiF to etch Ti3AlC2 to obtain Ti3C2Tx, adding a sulfur source to intercalate the Ti3C2Tx and enlarge the interlayer spacing of the Ti3C2Tx, adding a molybdenum source to polymerize the sulfur source to obtain a mixture solution, dipping a graphite felt in the mixture solution, drying, and pyrolyzing in a nitrogen atmosphere to obtain the high-activity graphite felt, according to the prepared high-activity graphite felt loaded Ti3C2Tx, active sites of reaction of vanadium ions are effectively increased, molybdenum oxide can catalyze mutual conversion of the vanadium ions, and the energy efficiency and the voltage efficiency of a vanadium battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of all-vanadium liquid flow battery electrodes, and in particular to a highly active graphite felt for a vanadium battery and a preparation method thereof. Background Art

[0002] The electrode is one of the core components of the all-vanadium flow battery. It does not participate in the reaction itself, but only provides active sites for the redox reaction of vanadium ions. Therefore, the electrode requirements for the all-vanadium flow battery are large specific surface area, good conductivity, high activity, and also require it to be resistant to strong acid and have good chemical stability. At present, carbon-based materials are used as the preferred electrode material for all-vanadium flow batteries. Among them, graphite felt can basically meet the above requirements, but it still has the disadvantages of low catalytic activity and electrochemical activity, which makes the energy efficiency and voltage efficiency of all-vanadium flow batteries low.

[0003] In view of this, we proposed a highly active graphite felt electrode and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a high-activity graphite felt for vanadium battery and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0005] The present invention provides the following technical solutions: A method for preparing highly active graphite felt for vanadium batteries comprises the following steps: Step S1: Add 5-7.5 parts by mass of lithium fluoride to 60-80 parts by mass of concentrated hydrochloric acid solution and stir to dissolve, then add 1 part by mass of titanium carbide, continue stirring for 48-72 hours, centrifuge and wash with deionized water and ethanol until the pH value of the product solution is 6-7, then centrifuge the product solution, precipitate and dry to obtain Ti3C2T x ; Step S2: Ti3C2T x Add to 80-100 parts by mass of ethanol and stir mechanically to disperse to obtain Ti3C2T x Ethanol solution; dissolving a sulfur source in ethanol to form a sulfur source solution; x 100 parts by weight of a sulfur source solution is added to the ethanol solution and stirred to form a dispersion; a molybdenum source is dissolved in deionized water to form a molybdenum source solution; 10 parts by weight of the molybdenum source solution is slowly added dropwise while stirring the dispersion to form a mixed solution; Step S3: stirring the mixed solution, immersing the graphite felt in the mixed solution, and drying to obtain a precursor graphite felt, and pyrolyzing the precursor graphite felt in a nitrogen atmosphere to obtain a highly active graphite felt.

[0006] Preferably, the sulfur source in step S2 is one of 1,2-benzenedithiol, 1,3-benzenedithiol and 1,4-benzenedithiol.

[0007] Preferably, the mass fraction of the sulfur source in the sulfur source solution in step S2 is 5%-10%.

[0008] Preferably, the molybdenum source in step S2 is one of phosphomolybdic acid and silicomolybdic acid.

[0009] Preferably, the mass fraction of the molybdenum source in the molybdenum source solution in step S2 is 5%-10%.

[0010] Preferably, in step S3, the heating rate of the heat treatment is 2-10°C / min, the holding temperature is 600-800°C, and the holding time is 1-3h.

[0011] A highly active graphite felt for vanadium battery is prepared by adopting the above-mentioned method for preparing the highly active graphite felt for vanadium battery.

[0012] The beneficial effects of the present invention include at least: Ti3C2T prepared by the present invention x The layered structure can not only provide more active sites for vanadium ion reactions, but also has a highly efficient catalytic effect on vanadium ion reactions, which is beneficial to improving the energy efficiency and voltage efficiency of vanadium batteries; In the present invention, the sulfur source is used to treat Ti3C2T x Intercalation reduces Ti3C2T x The stacking increases the Ti3C2T x The interlayer spacing of the sulfur source can be improved by S element doping after pyrolysis. The molybdenum oxide generated after the pyrolysis of the molybdenum source in the present invention has a catalytic effect on the vanadium ion reaction, which is beneficial to improving the energy efficiency and voltage efficiency of the vanadium battery. At the same time, the doping of phosphorus or silicon can improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a scanning electron microscope image of the graphite felt prepared in Example 4 of the present invention; Figure 2 This is the XRD spectrum of the catalyst on the surface of graphite felt fiber prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0014] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] A method for preparing highly active graphite felt for vanadium batteries comprises the following steps: Step S1: Add 5-7.5 parts by mass of lithium fluoride to 60-80 parts by mass of concentrated hydrochloric acid solution and stir to dissolve, then add 1 part by mass of titanium carbide, continue stirring for 48-72 hours, centrifuge and wash with deionized water and ethanol until the pH value of the product solution is 6-7, then centrifuge the product solution, precipitate and dry to obtain Ti3C2T x .

[0016] Step S2: Ti3C2T x Add to 80-100 parts by mass of ethanol and stir mechanically to disperse to obtain Ti3C2T x Ethanol solution; dissolving a sulfur source in ethanol to form a sulfur source solution; x 100 parts by mass of sulfur source solution are added to the ethanol solution and stirred and dispersed to form a dispersion; a molybdenum source is dissolved in deionized water to form a molybdenum source solution; 10 parts by mass of the molybdenum source solution are slowly added dropwise while stirring the dispersion to form a mixed solution; preferably, in step S2, the sulfur source is one of 1,2-benzenedithiol, 1,3-benzenedithiol, and 1,4-benzenedithiol. The mass fraction of the sulfur source in the sulfur source solution is 5%-10%. The molybdenum source is one of phosphomolybdic acid and silicomolybdic acid. The mass fraction of the molybdenum source in the molybdenum source solution is 5%-10%.

[0017] Step S3: Stir the mixed solution, immerse the graphite felt in the mixed solution, and then dry it to obtain a precursor graphite felt, and pyrolyze the precursor graphite felt in a nitrogen atmosphere to obtain a highly active graphite felt. The heat treatment heating rate is 2-10°C / min, the holding temperature is 600-800°C, and the holding time is 1-3h.

[0018] Example 1: Using the following scheme Step S1: 5 parts by mass of LiF were added to 60 parts by mass of concentrated hydrochloric acid solution and stirred to dissolve, and then 1 part by mass of Ti3AlC2 was added, and the stirring was continued for 48 hours. The product was centrifuged and washed with deionized water and ethanol until the pH of the product solution was 6-7, and the product was centrifuged and precipitated and dried to obtain Ti3C2T x ; Step S2: Ti3C2T x Disperse in 80g ethanol with mechanical stirring, disperse 10g 1,2-benzenedithiol in 90g ethanol to form 1,2-benzenedithiol solution, and add Ti3C2T x 100g of 1,2-benzenedithiol solution was added to the ethanol solution and dispersed with stirring to form a dispersion liquid. 1g of phosphomolybdic acid was dissolved in 9g of deionized water to form a phosphomolybdic acid solution. 10g of phosphomolybdic acid solution was slowly added dropwise while stirring the dispersion liquid to form a mixed solution. Step S3: Stir the mixed solution, immerse the graphite felt in the mixed solution, and then dry it to obtain a precursor graphite felt. Heat the precursor graphite felt to 600° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and pyrolyze it for 2 h to obtain highly active graphite felt.

[0019] Example 2: Using the following scheme Step S1: 7.5 parts by mass of LiF was added to 80 parts by mass of concentrated hydrochloric acid solution and stirred to dissolve, and then 1 part by mass of Ti3AlC2 was added, and the stirring was continued for 72 hours. The product was centrifuged and washed with deionized water and ethanol until the pH of the product solution was 6-7, and the product was centrifuged and precipitated and dried to obtain Ti3C2T x ; Step S2: Ti3C2T x Disperse in 100 g of ethanol and stir mechanically to disperse. Disperse 5 g of 1,3-benzenedithiol in 95 g of ethanol to form a 1,3-benzenedithiol solution, and add it to Ti3C2T x The mixture was stirred and dispersed in an ethanol solution to form a dispersion, 0.5 g of silicomolybdic acid was dissolved in 9.5 g of deionized water to form a silicomolybdic acid solution, and the solution was slowly added dropwise to the dispersion while stirring to form a mixed solution; Step S3: Stir the mixed solution, immerse the graphite felt in the mixed solution, and then dry it to obtain a precursor graphite felt. Heat the precursor graphite felt to 800° C. at a heating rate of 2° C. / min in a nitrogen atmosphere and pyrolyze it for 3 hours to obtain highly active graphite felt.

[0020] Example 3: Using the following scheme Step S1: 6 parts by mass of LiF were added to 70 parts by mass of concentrated hydrochloric acid solution and stirred to dissolve, and then 1 part by mass of Ti3AlC2 was added, and the stirring was continued for 60 hours. The product solution was centrifuged and washed with deionized water and ethanol until the pH of the product solution was 6-7, and the product solution was centrifuged and dried to obtain Ti3C2T x ; Step S2: Ti3C2T x Disperse in 90g ethanol with mechanical stirring at 1000r / min, disperse 6g 1,4-benzenedithiol in 94g ethanol to form 1,4-benzenedithiol solution, and add to Ti3C2T x The ethanol solution was stirred and dispersed to form a dispersion liquid, 0.8 g of phosphomolybdic acid was dissolved in 9.2 g of deionized water to form a phosphomolybdic acid solution, and the solution was slowly added dropwise to the dispersion liquid while stirring to form a mixed solution; Step S3: Stir the mixed solution, immerse the graphite felt in the mixed solution, and then dry it to obtain a precursor graphite felt. Heat the precursor graphite felt to 700° C. at a heating rate of 10° C. / min in a nitrogen atmosphere and pyrolyze it for 1 h to obtain highly active graphite felt.

[0021] Example 4: Using the following scheme Step S1: Add 5 parts by mass of LiF to 70 parts by mass of concentrated hydrochloric acid solution and stir to dissolve, then add 1 part by mass of Ti3AlC2, continue stirring for 48 hours, centrifuge and wash with deionized water and ethanol until the pH of the product solution is 6-7, then centrifuge the product solution, precipitate and dry to obtain Ti3C2T x ; Step S2: 3gTi3C2T x Disperse in 90 g of ethanol with mechanical stirring, disperse 7.1 g of 1,4-benzenedithiol in 92.9 g of ethanol to form a 1,4-benzenedithiol solution, and add it to Ti3C2T x In an ethanol solution, stir and disperse to form a dispersion liquid, dissolve 0.91 g of phosphomolybdic acid in 9.09 g of deionized water to form a phosphomolybdic acid solution, and slowly dropwise add the solution to the dispersion liquid while stirring to form a mixed solution; Step S3: Stir the mixed liquid, immerse the graphite felt in the mixed liquid, and then dry it to obtain a precursor graphite felt. Heat the precursor graphite felt to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere and pyrolyze it for 2h to obtain highly active graphite felt.

[0022] pass Figure 1 The scanning electron microscope image of graphite felt clearly shows that the surface of graphite felt fiber is wrapped by catalyst. Figure 2 The XRD spectrum of the catalyst on the surface of graphite felt fiber prepared in this example shows that there is Ti3C2T x The characteristic peaks of Ti3C2T x and MoO2 loaded on graphite felt.

[0023] Comparative Example 1: The preparation process is consistent with that of Example 1, except that no sulfur source is involved in step S1.

[0024] Comparative Example 2: The preparation process is consistent with that of Example 1, except that no molybdenum source is involved in step S2.

[0025] The graphite felts prepared in the embodiment and the comparative example were assembled into a stack, and a charge-discharge cycle test was performed under the same working conditions to record the coulombic efficiency, energy efficiency and voltage efficiency of the stack. The test results are shown in Table 1: Table 1. Test results of graphite felt performance in examples and comparative examples

[0026] The above test results show that compared with Comparative Example 1, Examples 1-4 have higher voltage efficiency and energy efficiency, which is mainly due to the fact that the sulfur source is used to treat Ti3C2T x Intercalation reduces Ti3C2T x The stacking increases the Ti3C2Tx The interlayer spacing is , and the S element doping after the sulfur source is pyrolyzed can improve the electrochemical performance; compared with Comparative Example 2, Examples 1-4 have higher voltage efficiency and energy efficiency. The molybdenum oxide generated after the pyrolysis of the molybdenum source in the present invention has a catalytic effect on the vanadium ion reaction, which is beneficial to improving the energy efficiency and voltage efficiency of the vanadium battery. At the same time, the doping of phosphorus or silicon can improve the electrochemical performance.

[0027] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing highly active graphite felt for vanadium batteries, characterized in that: The following steps are involved: Step S1: Add 5-7.5 parts by mass of lithium fluoride to 60-80 parts by mass of concentrated hydrochloric acid solution and stir to dissolve, then add 1 part by mass of titanium carbide, continue stirring for 48-72 hours, centrifuge and wash with deionized water and ethanol until the pH value of the product solution is 6-7, then centrifuge the product solution, precipitate and dry to obtain Ti3C2T x ; Step S2: Ti3C2T x Add to 80-100 parts by mass of ethanol and stir mechanically to disperse to obtain Ti3C2T x Ethanol solution; dissolving a sulfur source in ethanol to form a sulfur source solution; x 100 parts by weight of a sulfur source solution is added to the ethanol solution and stirred to form a dispersion; a molybdenum source is dissolved in deionized water to form a molybdenum source solution; 10 parts by weight of the molybdenum source solution is slowly added dropwise while stirring the dispersion to form a mixed solution; Step S3: stirring the mixed solution, immersing the graphite felt in the mixed solution, and drying to obtain a precursor graphite felt, and pyrolyzing the precursor graphite felt in a nitrogen atmosphere to obtain a highly active graphite felt.

2. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: In step S2, the sulfur source is one of 1,2-benzenedithiol, 1,3-benzenedithiol and 1,4-benzenedithiol.

3. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: The mass fraction of the sulfur source in the sulfur source solution in step S2 is 5%-10%.

4. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: In step S2, the molybdenum source is one of phosphomolybdic acid and silicomolybdic acid.

5. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: The mass fraction of the molybdenum source in the molybdenum source solution in step S2 is 5%-10%.

6. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: In step S3, the heating rate of the heat treatment is 2-10°C / min, the holding temperature is 600-800°C, and the holding time is 1-3h.

7. A highly active graphite felt for vanadium batteries, characterized in that: The highly active graphite felt is prepared by the method for preparing highly active graphite felt for vanadium batteries according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • All-vanadium-redox-flow-battery electrode material and preparing method thereof

    CN106410219A

  • Nitrogen and phosphorus co-doped carbon coated MoO3-x and preparation method thereof

    CN108390048A

  • Sulfur-doped MXene negative electrode material as well as preparation method and application thereof

    CN109817921A

  • Preparation method, product and application of nitrogen-doped MXene loaded molybdenum disulfide composite material

    CN114512653A